KEPUASAN PELAYANAN RAWAT INAP RUMAH SAKIT UMUM DAERAH MERAUKE PROVINSI PAPUA - TETHOOL, HENDRIK; OGOTAN, MARTHA; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
Service and satisfaction are two things that cannot be separated, because with satisfaction,the relevant parties can correct each other until the services provided are better or worse. It is very influencedby every officer in providing services, in other words, services that can be satisfying are services carried outbased on applicable provisions and can understand what is being asked by the community from thedepartment of service itself. Patient satisfaction is a major challenge in the provision of health servicestoday. In general, plenary health services are health services that include promotive (health improvement),preventive (prevention), curative (treatment), and rehabilitative (recovery). (Law No. 44 of 2009 concerningHospitals). In Law No. 25 of 2009 concerning public services, in Article 18 it is explained that the communityhas the right to obtain quality services in accordance with the principles and objectives of the service.Keywords: Satisfaction, Service, and Hospitalization